Baicalein ameliorates DSS-induced ulcerative colitis in mice by inhibiting ferroptosis and regulating gut microbiota - Lv, Weiguang; Han, Shengnan; Li, Ke; Yan, Aimin; Wang, Wei; Lu, Wanping; Han, Jing; Zhang, Chenggang (Frontiers in Pharmacology, 2025)
Ulcerative colitis (UC) is a nonspecific inflammatory disease. Baicalein has potential value in treating UC, but its mechanism is unclear. This study aims to evaluate the protective effects of baicalein on dextran sodium sulfate (DSS)-induced UC mice. The UC model was established by 4% DSS solution for 7 days. Treatments included baicalein (10 mg/kg, 20 mg/kg) and sulfasalazine (200 mg/kg) via oral gavage. Colonic damage was assessed through body weight, disease activity index (DAI), histopathology (H&E staining) and colon length. Inflammatory cytokines were measured by ELISA, while oxidative stress markers and iron content were analyzed by colorimetric assays. Protein expression was evaluated by Western blot, and gene levels by RT-qPCR. Intestinal microbiota changes were characterized using 16S rRNA gene sequencing. Results demonstrated that Baicalein ameliorated UC mice, particularly in high-dose of baicalein group. After baicalein treatment, the proinflammatory cytokines (TNF-α, IL-1β), and anti-inflammatory cytokine (IL-10) has decreased. Additionally, high-dose of baicalein strongly reversed oxidative stress alterations caused by DSS, as evidenced by Fe2+, MDA, ROS significantly depleted, and MPO, SOD, GSH significantly increased. Protein and mRNA expression analyses revealed that high-dose baicalein upregulated the expression of FTH1, GPX4, SLC7A11, SLC3A2 and Nrf2, while downregulating ACSL4 significantly. Microbiological analysis showed that baicalein ameliorated intestinal dysbiosis, increased Ligilactobacillus and NK4A136, while reduced Clostridium_sensu_stricto_1 and Escherichia-Shigella. These findings suggest that baicalein mitigates DSS-induced UC mice by reducing oxidative stress and inflammation, suppressing ferroptosis and modulating gut microbiota composition, Proposing a potentially effective therapeutic approach for UC.